PERSPECTIVES OF DEVELOPMENT OF THE HIGHER EDUCATION SYSTEM OF ARMENIA: HUMANIZATION OR HUMANITARIZATION? - Берберян , А.С. (Արդի հոգեբանություն, 2025)
The article examines humanistic approaches to Armenia's educational policy. The idea is stated that more productive personal and professional development of specialists can be ensured by introducing the component of personal development education into the educational process of the university. The purpose of our research is to identify the readiness of subjects of educational activity for humanization, personally oriented activities. The results of the conducted empirical studies testify to the need to identify the parameters of the preparedness of the humanistic position of the subjects of educational activity.